Extended objects as ultradistribution-marked configuration spaces - Mendes, Rui Vilela (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9 Configuration spaces of point particles with and without internal quantum numbers (marks) were studies earlier as a framework for the description of the dynamics of multiagent systems. Here, we propose to extend this framework to configuration spaces of extended objects of any shape. This is attained by identifying the shape with the support of an ultradistribution of compact support. Then, by using the multipole expansion property of these ultradistributions, we conclude that the configuration spaces of extended objects are a simple extension of the marked configuration spaces.